A multi-functional dentine bonding system combining a phosphate monomer with eugenyl methacrylate. Issue 6 (June 2022) - Alkattan, Rana; Banerji, Subir; Deb, Sanjukta
Abstract: Objective: The tooth-resin composite interface is frequently associated with failure because of microbial contamination, hydrolytic and collagenolytic degradation. Thus, designing a dentine bonding system (DBS) with an intrinsically antimicrobial polymerisable monomer is of significance especially if it can be used with self-etching primers enabling resistance to degradation of the interface. Methods: Experimental adhesives were developed incorporating eugenyl methacrylate (EgMA) at concentrations of 0, 10 or 20 wt%, designated as EgMA0, EgMA10 and EgMA20, respectively, for use as a two-step self-etch DBS with the functional monomer bis[2-(methacryloyloxy) ethyl] phosphate (BMEP) in the primer. The curing, thermal and wettability properties of the adhesives were determined, and hybrid layer formation was characterised by confocal laser scanning microscopy, microtensile bond strengths (µTBS) and nanoleakage by back-scattered SEM. In situ zymography was used to assess MMP inhibitory activity of the BMEP-EgMA DBS. Results: EgMA in the adhesives lowered the polymerisation exotherm and resulted in higher Tg, without negatively affecting degree of conversion. Water sorption and solubility were significantly lower with higher concentrations of EgMA in the adhesive. The formation of a distinct hybrid layer was evident from confocal images with the different adhesives, whilst EgMA20 yielded the highest µTBS post water storage challenges and lowest nanoleakage after 6 months. The experimental DBS exhibited minimal to no MMP activity at 3 months. Significance: The hydrophobic nature of EgMA and high cross-link density exerts considerable benefits in lowering water uptake and polymerisation exotherm. The application of EgMA, adhesives in conjunction with BMEP in a multi-functional self-etching DBS can resist MMP activity, hence, enhance longevity of the dentine-resin composite interface. Highlights: Reduced water uptake of EgMA adhesives can minimise hydrolysis of the hybrid layer. The hydrophobicity & cross-link density of EgMA enhance dentine bond durability. EgMA adhesives have no adverse effects on the anti-collagenolytic activity of BMEP. Multi-functional DBS with antibacterial & anti-MMP activity can improve longevity.